GEOCHEMICAL EVIDENCES FOR PROTOLITH ORIGIN OF FE-AND AL-RICH METAPELITES FROM KUZNETSK ALATAU AND YENISEY RIDGE - Likhanov I.I.; Reverdatto V.V.; Vershinin A.E. (My University, 2006)
Analysis of new geochemical information of distribution of petrogenetic and rare, including rare-earth, elements in Fe- and Al-rich metapelites of the Korda (Yenisei Ridge) and Amar (Kuznetsk Alatau) Formations gave a clue to the reconstruction of the composition and origin of their protoliths. It has been established that these rocks are the redeposited and metamorphosed products of the Precambrian kaolinite-type crusts of weathering, while petro- and geochemical differences between them are due, chiefly, to different conditions of formation. The protolith of the Korda Formation metapelites was produced by erosion of the post-Archean complexes of rocks chiefly of granitoid composition and accumulation in continental-margin shallow basins in the conditions of humid climate. Geochemical characteristics of deeper primary deposits of the Amar Formation suggest a dominating role of volcanogenic material of basic composition in the erosion zone. These results agree with data of lithological-facies analysis and geodynamic reconstructions of evolution of geological complexes of the Yenisei Ridge in the Middle Riphean and of the Kuznetsk Alatau in the Vendian. A conclusion is made that rare-earth elements had limited migration mobility during contact and collisional metamorphism.